Harvest residues of maize, wheat and sunflower - waste, or the source of valuable raw materials? - Project PhAgroWaste - Maksimović, Zoran (Archives of Pharmacy, 2022)
In Serbia, agricultural waste is still an underutilized resource. Recently, a trend of harvest residues open burning in the fields has been observed, resulting in heavy air pollution and posing risk to human and ecological health. Therefore, a consistent set of interdisciplinary investigations under the title “Value-Added Products from Maize, Wheat and Sunflower Waste as Raw Materials for Pharmaceutical and Food Industry” (PhAgroWaste) has been designed, with the aim to investigate and propose a cost-effective and sustainable agricultural waste management practice, where micro- and nanocrystalline cellulose (MCC/NCC) and the other products of high commercial value and biological activity (waxes, polyphenol-containing extracts and/or isolated chemical compounds) will be produced from harvest residues of corn, wheat and sunflower. MCC is one of the most frequently used excipients in formulations of different pharmaceutical products. On the other hand, NCC finds applications in tissue engineering, 3D-bioprinting, waste water treatment, development of composite materials, drug delivery, etc. MCC and polyphenol-rich extracts produced from agricultural waste will be added to innovative formulations of meat products to gain higher oxidative stability, extend shelf life, improve fatty acid composition and increase fibres content. Waxes and polyphenol-rich extracts will be tested in new formulations of nature-inspired cosmetics. This way, high value-added products can be created, with intention to improve the quality of life of their consumers, to reduce waste in the production chain, to limit environmental impacts of intensive agriculture and to improve competitiveness and economic growth in Serbian food and pharmaceutical industry.